The Regional Representative Council of The Republic of Indonesia and Civil Security Governance: Bridging Political Polarization in The Special Capital Region of Jakarta - Hamdi, Abdul Aziz; Widodo, Pujo; G. Samudro, Eko; Setiawibawa, Rachmat; Uksan, Ariifuddin (Cita konsultindo, 2026)
This study examines the role of the Regional Representative Council of the Republic of Indonesia (DPD RI) in civil security governance and its contribution to mitigating political polarization in the Special Capital Region of Jakarta. Drawing on Collaborative Governance Theory, the study conceptualizes security and political stability as outcomes of coordinated interaction among representative institutions, security actors, and governance processes rather than hierarchical control. Using a qualitative descriptive approach based on document analysis of official records, policy reports, and relevant academic literature, the study analyzes how the DPD RI exercises oversight, coordination, regional representation, and policy advocacy in security-related and politically sensitive contexts. The findings indicate that the DPD RI contributes to civil security governance by institutionalizing non-operational oversight, facilitating inter-institutional coordination, and enhancing democratic accountability within the security sector. In addition, the Council plays a bridging role in mitigating political polarization by articulating regional aspirations, maintaining center–region balance, and advancing non-partisan policy recommendations that address structural sources of political division. The study concludes that representative institutions operating outside party-based competition can significantly support civil security governance and political cohesion through collaborative and facilitative governance mechanisms in plural democratic settings.